Proteolysis of the human DNA polymerase delta smallest subunit p12 by μ-calpain in calcium-triggered apoptotic HeLa cells. - Xiaoting Fan; Qian Zhang; Chao You; Yuanxia Qian; Jing Gao; Peng Liu; Huiqing Chen; Huifang Song; Yan Chen; Keping Chen; Yajing Zhou (PLoS ONE)
Degradation of p12 subunit of human DNA polymerase delta (Pol δ) that results in an interconversion between Pol δ4 and Pol δ3 forms plays a significant role in response to replication stress or genotoxic agents triggered DNA damage. Also, the p12 is readily degraded by human calpain in vitro. However, little has been done for the investigation of its degree of participation in any of the more common apoptosis. Here, we first report that the p12 subunit is a substrate of μ-calpain. In calcium-triggered apoptotic HeLa cells, the p12 is degraded at 12 hours post-induction (hpi), restored thereafter by 24 hpi, and then depleted again after 36 hpi in a time-dependent manner while the other three subunits are not affected. It suggests a dual function of Pol δ by its interconversion between Pol δ4 and Pol δ3 that is involved in a novel unknown apoptosis mechanism. The proteolysis of p12 could be efficiently blocked by both calpain inhibitor ALLN and proteasome inhibitor MG132. In vitro pull down and co-immunoprecipitation assays show that the μ-calpain binds to p12 through the interaction of μ-calpain with Pol δ other three subunits, not p12 itself, and PCNA, implying that the proteolysis of p12 by μ-calpain might be through a Pol δ4/PCNA complex. The p12 cleavage sites by μ-calpain are further determined as the location within a 16-amino acids peptide 28-43 by in vitro cleavage assays. Thus, the p12/Pol δ is a target as a nuclear substrate of μ-calpain in a calcium-triggered apoptosis and appears to be a potential marker in the study of the chemotherapy of cancer therapies.